THE INFLUENCE OF LEARNING VIDEO TUTORIAL ON LEARNING ACJIEVEMENT - Lis Parida; Bambang Sahono; Johanes Sapri (UNIB Press, 2018)
The purpose of this study was to determine the effect of video tutorial learning on student learning achievement. The experimental design was used in this study. There were 48 students consists of 20 men and 28 women as respondents in the study. Data collection uses multiple choice objective tests with 5 answer choices. Test questions have been tested to see their validity and reliability. Data analysis using statistical assistance, namely the t test. The results of the study show that there is an influence of learning by using tutorial videos on student learning achievement. The use of tutorial videos in learning can be applied to other fields of study.